Perhitungan Harga Pokok Produksi Berbasis Aktivitas Pada Umkm Al-Iqshan Pastry Dan Bakery - Cindea Corycha Putri; Ade Nila Oktafiani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This study aims to determine the difference in the calculation of the Cost of Production between conventional and activity-based methods if applied by Al Iqshan Pastry and Bakery, which by knowing the comparison of the Cost of Production will make it easier for management to get an estimate of the costs incurred during production and will facilitate the management in making reports, and with an accurate cost report the management can make the right decisions for the benefit of the company. In calculating the Cost of Production applied by Al Iqshan Pastry and Bakery using conventional and activity-based methods. Cost of Production is calculated on the production of brown bread, meses bread, milk chese read, chocolate banana bread, cappuccino bread in 2021.This study shows that in the analysis of product costs based on activity, understanding the characteristics of a cost becomes very important.